2007 GUIDELINES FOR THE MANAGEMENT OF ARTERIAL HYPERTENSION (ENDING) (Рациональная фармакотерапия в кардиологии, 2016)
The Task Force for the Management of Arterial Hypertension of the European Society of Hypertension and of the European Society of Cardiology.